FAKTOR - FAKTOR PENENTU TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH PROVINSI DI INDONESIA - Intan Cristiana; Maryono Maryono (Faculty of Economic and Business Universitas STIKUBANK, 2016)
This research aims to investigate and analyze factors that influence provincial government disclosurefiscal years 2013-2015. Disclosure of goverment financial statements is a form of goverment transparency and accountabilit, but many local goverments do not disclose the full financial statements. Population of this research are provincial goverment financial statements in Indonesia fiscal year 2013-2015 based on Government Accounting Standard. Samples are included in the criteria of this study were 101 financial statements using purposive sampling method. This research data analysis methods using the multiple linear regression analysis by SPSS 23.0. The results showed that realized of revenue and number of units under Provincial (SKPD) have positiveand significant influence on the disclosure level of provincial government financial statements. While total asset have negative effect and significant influence on the disclosure level of provincial government financial statements. However, the level of dependence,population, number of audit findings and level of financial irregularities do not significantly influence the disclosure level of provincial government financial statements. Keywords: Influence provincial government disclosure, BPK audit results, Government Accounting Standard.